Neonatal Tracheostomies: Changing Trends. (2nd September 2014) - Fisher, Kelly; Isaiah, Amal; Pereira, Kevin D.
Abstract : Objectives: (1) Examine the current trends in neonatal tracheostomies and compare them to historic cohorts. (2) Determine and stratify the current risk factors for failed extubation in the neonatal intensive care unit (NICU). Methods: We conducted a retrospective review of 34 consecutive neonatal tracheostomies performed over a 5‐year period (2008‐2012) in a university‐based tertiary care hospital. Risk factors for failed extubation were identified and analyzed. Results: Sixty‐two percent of the infants had identifiable anatomic causes of airway obstruction, whereas the remaining (38%) had significant isolated pulmonary disease ( P <. 05; χ 2 test). The vast majority (95%) of the tracheostomies were performed at age ≥30 days (mean = 129d, SD = 101). Within anatomic risk factors, subglottic obstruction represented the largest group (33%). Risk of extubation failure was not systematically related to either birth weight ( P =. 3 to. 9; n‐way analysis of variance) or age ( P =. 1 to. 5) separately. Within a small group (n = 5) both anatomic causes as well as pulmonary disease were present. No procedure‐related complications were encountered. Conclusions: Neonatal tracheostomies are currently being performed for anatomic airway abnormalities more frequently than primary pulmonary disease as previously documented. It suggests that current respiratory therapies have lowered the burden of chronic lung disease. Even as more low‐birth‐weight neonates are being rescued, the presence of multiple concurrent risk factors did not appear to increase the chances of extubation failure or need for tracheostomy within this population.